The role of community-based tourism for mangroves conservation in Banten, Indonesia - Nuraeni, Eni; Kusum, Yayan Wahyu C (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Mangroves provide multiple ecological functions such as connectors and balancers of land and sea ecosystems. The presence of mangroves in coastal areas is very important for reducing the impact of tsunamis and tidal flooding. The role of local communities in the form of community-based tourism models, in conserving mangrove forests has not been extensively studied. This study aims to fill the gap in evaluating local communities’ involvement, particularly under the tourism-based communities’ model, in conserving mangroves and, at the same time, gaining economic benefits. This study was conducted in the mangrove villages of “Patikang,” Citeureup Village, and Pandeglang Regency. This study applied mixed methods that combine both quantitative and qualitative approaches. Primary data were obtained directly from the local community through using questionnaires, interviews, and field observations. Secondary data collection was carried out through a literature review of mangrove conservation and community development in coastal areas. Our study found that local community-based tourism namely “Putri Gundul” played a very important role in increasing community awareness to conserve mangrove forests. The community has gained more knowledge on the biology of mangrove species and the ecology of mangroves for mangrove restoration. Furthermore, the involvement of local communities in mangrove conservation and restoration can increase the economy of communities by producing various products from mangroves.